Professionalization of the Role of University Teachers: Classroom Observation as a Tool for Fostering Competence Development - Adamska-Chudzińska, Małgorzata (Roczniki Nauk Społecznych, 2025)
Performing the professional role of an academic teacher requires making a constant effort to improve one’s teaching competence and adjust flexibly to the ever-changing reality of education. The paper aims to demonstrate that classroom observation based on the constructivist model with the use of adequate tools may serve as an essential instrument of support for the professional development of academic educators. The method chosen is that of participant observation and analysis of classroom observation records. A total of 810 observation hours and documentation prepared by 220 observed participants at the Study for Academic Teaching Excellence of Krakow University of Economics were subject to analysis and research. A proposal for an observation report card was developed, as it plays a vital part in observation and prepares the observer to prompt a post-observation discussion. A holistic, three-stage framework of the classroom observation process is shown to be necessary. Emphasis was also placed on the major significance of a post-observation discussion aimed at stimulating observed trainees to reflect on their teaching skills and qualifications, and to individually devise a competence development plan.